Der Zusammenhang von Bindungsrepräsentationen zwischen Pflegeeltern und Pflegekindern unter Berücksichtigung von Geschlechterunterschieden - Nowacki, Katja; Kliewer, Josephine; Bovenschen, Ina; Lang, Katrin; Zimmermann, Janin; Spangler, Gottfried (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2015)

Foster children’s attachment behavior and representation: Influence of children’s pre-placement experiences and foster caregiver’s sensitivity - Bovenschen, Ina; Lang, Katrin; Zimmermann, Janin; Förthner, Judith; Nowacki, Katja; Roland, I.; Spangler, Gottfried (Child Abuse & Neglect, 2015)

Foster Children‘s Attachment Security and Behavior Problems in the First Six Months of Placement: Associations with Foster Parents’ Stress and Sensitivity - Gabler, Sandra; Bovenschen, Ina; Lang, Katrin; Zimmermann, Janin; Nowacki, Katja; Kliewer, Josephine; Spangler, Gottfried (Attachment and Human Development, 2014)

Foster children’s attachment security in the first year after placement: A longitudinal study of predictors. - Lang, Katrin; Bovenschen, Ina; Gabler, Sandra; Zimmermann, Janin; Nowacki, Katja; Kliewer, Josephine; Spangler, Gottfried (Early Childhood Research Quarterly, 2016)

Interviewtechnik zur Erfassung von Bindungsstörungen. - Kliewer, Josephine; Bovenschen, Ina; Roland, I.; Lang, Katrin; Spangler, Gottfried; Nowacki, Katja (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2015)

Predictors of foster parents’ stress and associations to sensitivity in the first year after placement - Gabler, Sandra; Kungl, Melanie; Bovenschen, Ina; Lang, Katrin; Zimmermann, Janin; Nowacki, Katja; Kliewer-Neumann, Josephine; Spangler, Gottfried (Child Abuse & Neglect, 2018)
In Germany, almost 70 000 children are living in foster families (Statistisches Bundesamt, 2016). Many foster children show mental health problems as they were exposed to an accumulation of risk factors. Hence, foster parents are often faced with challenging parenting situations. The current study focuses on the predictors of foster parents’ stress and examines longitudinally whether parenting stress is associated with foster parents’ sensitivity. The sample consisted of 55 children (aged from 1 to 6 years) and their foster caregivers. Foster parents’ sensitivity was observed during home visits. Caregiver reports were used to assess parenting stress (Parenting Stress Index) as well as foster children's externalizing behavior problems (Child Behavior Checklist). For main caregivers’ stress at the beginning of placement, regression analyses revealed both, foster children's externalizing problems as well as partners’ stress as predictive. For main caregivers’ stress one year after, only initial parenting stress and partners’ stress were predictive. Foster parents’ sensitivity was correlated with their parenting stress one year after placement. Regression analyses revealed no longitudinal effects of initial parenting stress on overall sensitivity. However, supportive presence was predicted by initial supportive presence and by the interaction between parenting stress and children's externalizing problems at placement. The findings highlight the role of the partner in experiencing parenting stress when taking care of a foster child. Furthermore, they emphasize that foster parents who care for children with behavior problems need adequate support that can buffer initial parenting stress and thereby promote sensitive caregiving.
Created from Fastlane, Scopus look-up
Keywords: Behavior problems; Foster children; Foster parents; Parenting stress; Sensitivity

Predictors of the rate and course of reactive attachment disorder and disinhibited social engagement disorder symptoms in foster children during the first year of placement - Zimmermann, Janin; Kliewer-Neumann, Josephine; Bovenschen, Ina; Lang, Katrin; Gabler, Sandra; Nowacki, Katja; Spangler, Gottfried (Child Abuse & Neglect, 2024)
Background: Due to adverse care experiences, foster children are at risk for developing symptoms of reactive attachment disorder (RAD) and disinhibited social engagement disorder (DSED). Objective: This study investigated the factors influencing rate and course of RAD and DSED symptoms during the first year of placement in long-term foster care. Participants and setting: The sample consisted of 55 foster children aged 1 to 6 years. Measurements were taken at placement as well as 6 and 12 months after placement. Methods: RAD and DSED symptoms were assessed with the Disturbance of Attachment Interview (DAI). DSED symptoms were also assessed by observation with the Rating of Infant Stranger Engagement (RISE). Foster parents and caseworkers reported on children's preplacement experiences and placement characteristics. Results: RAD symptoms were rare at Wave 1 (5.5 %) and remitted in most children within the first six months of placement, t(54) = 3.06, p =.003. A total of 30.9 % of the foster children presented DSED symptoms according to the DAI, but only 5.5 % of the children according to the RISE. Foster parents reported symptom reduction, t(54) = 3.71, p =.003, while observational data indicated symptom stability. Prior placement in emergency foster care was associated with lower levels of RAD at Wave 1, F(1.62, 80.88) = 7.80, p =.002, while later placed children presented more RAD and DSED symptoms (RRAD2 = 0.07, RDSED2 = 0.08, RRISE2 = 0.12). Psychopathology of the biological parents (RRAD2 = 0.07, RDSED2 = 0.08) and visitation with the biological parents (RRISE2 = 0.14) predicted symptom stability. Conclusion: A substantial number of foster children present persistent DSED symptoms indicating a need for evidenced based interventions.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Adverse childhood experiences; Disinhibited social engagement disorder; Foster children; Mental health; Neglect; Reactive attachment disorder